On the use of the repeated-sprint training in hypoxia in tennis - Brechbuhl, C.; Brocherie, F.; Wills, S. J.; Schmitt, L.; Blokker, T.; Girard, O.; Montalvan, B. (Frontiers in Physiology, 2020)
Purpose:To examine physiological and technical responses to repeated-sprint training in normobaric hypoxia at ~3,000 m (RSH, n = 11) or in normoxia (RSN, n = 11) compared to a control group (CON, n = 8) in well-trained tennis players. Participants were 28.8 ± 5.9 years old without any previous experience of training in hypoxia.Methods In addition to maintaining their usual training (CON), both RSH and RSN groups completed five tennis specific repeated-shuttle sprint sessions (4 × 5 × ~8 s maximal sprints with ~22 s passive recovery and ~5 min rest between sets) over 12 days. Before (Pre), the week after (Post-1) and 3 weeks after Post-1 (Post-2), physical/technical performance during Test to Exhaustion Specific to Tennis (TEST), repeated-sprint ability (RSA) (8 × ~20 m shuttle runs—departing every 20 s) and heart rate variability (HRV) were assessed. Results: From Pre to Post-1 and Post-2, RSH improved TEST time to exhaustion (+18.2 and +17.3%; both P < 0.001), while the "onset of blood lactate accumulation" at 4 mmol L-1 occurred at later stages (+24.4 and +19.8%, both P < 0.01). At the same time points, ball accuracy at 100% V?O2max increased in RSH only (+38.2%, P = 0.003 and +40.9%, P = 0.007). Markers of TEST performance did not change for both RSN and CON. Compared to Pre, RSA total time increased significantly at Post-1 and Post-2 (-1.9 and -2.5%, P < 0.05) in RSH only and this was accompanied by larger absolute delta total hemoglobin (+82.5 and +137%, both P < 0.001). HRV did not change either supine or standing positions.Conclusion Five repeated sprint training sessions in hypoxia using tennis specific shuttle runs improve physiological and technical responses to TEST, RSA, and accompanying muscle perfusion responses in well-trained tennis players.